Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1002/1099-1573(200008)14:5<333::aid-ptr584>3.3.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

A phase I trial of andrographolide in HIV positive patients and normal volunteers

Abstract: A phase I dose-escalating clinical trial of andrographolide from Andrographis paniculata was conducted in 13 HIV positive patients and five HIV uninfected, healthy volunteers. The objectives were primarily to assess safety and tolerability and secondarily to assess effects on plasma virion HIV-1 RNA levels and CD4(+) lymphocyte levels. No subjects used antiretroviral medications during the trial. Those with liver or renal abnormalities were excluded. The planned regimen was 5 mg/kg bodyweight for 3 weeks, esca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
111
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(113 citation statements)
references
References 0 publications
1
111
0
1
Order By: Relevance
“…Andrographolide is bitter crystalline compound, colorless having antithrombotic, hyphoglycemic and antipyretic properties. A recent study conducted by USA University that this plant is having anti HIV activity (Calabrese, 2000). This plant ranks seventeenth position among their thirty two prioritized medicinal plants and annual growth of this plant is 3.1 percent (Anonymous, 2007).…”
Section: Introductionsupporting
confidence: 89%
“…Andrographolide is bitter crystalline compound, colorless having antithrombotic, hyphoglycemic and antipyretic properties. A recent study conducted by USA University that this plant is having anti HIV activity (Calabrese, 2000). This plant ranks seventeenth position among their thirty two prioritized medicinal plants and annual growth of this plant is 3.1 percent (Anonymous, 2007).…”
Section: Introductionsupporting
confidence: 89%
“…1), is one of the main active constituents of Andrographis paniculate (BURM) NEES, a famous traditional Chinese medicine. Andrographolide has many bioactivities, such as antiinflammatory and antimicrobial, 1,2) antiplatelet aggregation, 3,4) hepatoprotective, 5,6) and anti-human immunodeficiency virus (HIV) activity. 7) Andrographolide is widely used clinically with good results, but it did not show efficacy in activity assays in vitro.…”
mentioning
confidence: 99%
“…It was found that andrographolide had wide bioactivities, such as anti-inflammatory antibiotic (Sinha et al, 2000;Shen et al, 2002), anti-platelet aggregation (Zhang and Tan, 1997;Amroyan et al, 1999), and anti-human immunodeficiency virus activities (Calabrese et al, 2000). Andrographolide was widely used in the clinic, but it was not effective in vitro.…”
mentioning
confidence: 99%